2017
DOI: 10.1016/s0140-6736(16)31595-1
|View full text |Cite|
|
Sign up to set email alerts
|

Post-listing survival for highly sensitised patients on the UK kidney transplant waiting list: a matched cohort analysis

Abstract: UK National Health Service Blood & Transplant and Guy's & St Thomas' National Institute for Health Research Biomedical Research Centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 24 publications
2
71
2
Order By: Relevance
“…Recipients of kidney transplants from incompatible live donors had a higher survival rate than either control group at 1 year (95.0% vs. 94.0% for the waiting list or transplant control group and 89.6% for the waiting list‐only control group), 3 years (91.7% vs. 83.6% and 72.7%, respectively), 5 years (86.0% vs. 74.4% and 59.2%) and 8 years (76.5% vs. 62.9% and 43.9%) ( P < 0.001 for all comparisons with the two control groups). These results contrast the analysis of the UK adult transplant waiting list that compared the patient survival of crossmatch‐positive living donor HLA‐incompatible kidney transplant with that of similarly sensitized patients awaiting a compatible organ . Two hundred and thirteen patients who underwent HLA‐incompatible transplant were matched in a 1:4 ratio with similarly sensitized patients listed for a transplant across the same time period.…”
Section: Benefits Of Desensitizationmentioning
confidence: 71%
“…Recipients of kidney transplants from incompatible live donors had a higher survival rate than either control group at 1 year (95.0% vs. 94.0% for the waiting list or transplant control group and 89.6% for the waiting list‐only control group), 3 years (91.7% vs. 83.6% and 72.7%, respectively), 5 years (86.0% vs. 74.4% and 59.2%) and 8 years (76.5% vs. 62.9% and 43.9%) ( P < 0.001 for all comparisons with the two control groups). These results contrast the analysis of the UK adult transplant waiting list that compared the patient survival of crossmatch‐positive living donor HLA‐incompatible kidney transplant with that of similarly sensitized patients awaiting a compatible organ . Two hundred and thirteen patients who underwent HLA‐incompatible transplant were matched in a 1:4 ratio with similarly sensitized patients listed for a transplant across the same time period.…”
Section: Benefits Of Desensitizationmentioning
confidence: 71%
“…The greater consideration, however, is that the overall risk of transplanting must be balanced against the risk of not transplanting for each patient, with the prognosis from their end‐stage organ failure being the main driver of the latter. This may vary according to the organ involved, the patient's clinical status or the quality of care available . In this context, it may be appropriate to accept increased immunological risk in transplantation because of the magnitude of the risk of harm faced by an individual if they are not transplanted .…”
Section: Management Of Pre‐existing Dsamentioning
confidence: 99%
“…This adaptation of immunosuppression has allowed successful transplantation to occur despite the presence of HLA DSA, with outcomes that are superior to potential recipients who continued to wait for a compatible transplant in some programmes . However, in others, the benefit seems less clear . This further highlights the importance of balancing the risk of transplanting against the risk of not transplanting when making personalised decisions for each recipient.…”
Section: Management Of Pre‐existing Dsamentioning
confidence: 99%
“…However, a similar study from the United Kingdom showed no survival benefit for ILDKT over waitlisting and subsequent transplantation. 5 The reasons for these discrepant findings were analyzed in detail and included differences in definitions of sensitization, control groups, and inferior dialysis outcomes in the United States compared with many other developed countries. 6 With the demonstrated benefit of extended hours of hemodialysis, patients facing a lengthy wait for transplantation should be considered for this mode of dialysis 7 -providing the greatest likelihood of survival until the time of transplantation, and greater fitness to meet the challenges of surgery and immunosuppression.…”
Section: Overcoming Preexisting Alloantibody In Renal Transplantationmentioning
confidence: 99%